المسؤولية عن مخاطر التطور التكنولوجي - غزال, حمود; حسن, الهيثم (Latakia University Journal - Economic and Legal Sciences Series, 2019)
لقد كان من نتاج الطفرة التكنولوجية التي تحققت على إثر الثورة الصناعية ازدحام الأسواق بأشكال من المنتجات لم تكن معهودة من ذي قبل. ولا شك في أنّ التطور التكنولوجي كان مصدراً لأنواع جديدة من الحوادث التي يتعرض لها المستهلكون في استخدامهم واقتنائهم للمنتجات. وصحيح أن المنتجات في يومنا هذا تجلب السعادة والرخاء للمستهلك، لكنها في الوقت نفسه تشكل مصدر مخاطر كامنة تهدد حياته؛ وقد لا يكون من الممكن اكتشافها في حدود المعرفة العلمية والفنية السائدة وقت طرح المنتَج للتداول. الأمر الذي يُثير التساؤل عن مدى إمكانية مسائلة المنتج عن الأضرار التي قد يحدثها المنتج بسبب وجود عيوب فيه لم تكن تسمح المعرفة العلمية والفنية وقت طرح المنتَج للتداول باكتشافه. The market was overwhelmed with many types of products which were not common before. And that was because of the technical rush which was resulted by the industrial revolution. There is no doubt that the technological development was a source for new kinds of consumer accidents during the use or possession of these product. In fact, products nowadays bring happiness and prosperity to consumers, but they form a source of perils that threaten their lives. These perils could not have been discovered before due to the lack of scientific and technical knowledge when the product was produced and circulated. That makes us wonder about the possibility of determining the responsibility of the producer for the damages caused by product defects which could not be discovered under the available scientific and technical knowledge at that time.